# CONVERTING A QUADRATIC EQUATION FROM STANDARD TO VERTEX FORM WORKSHEET

Write each function in vertex form :

Problem 1 :

y = x2 - 6x + 3

Solution

Problem 2 :

y = x2 + 2x + 7

Solution

Problem 3 :

y = x2 + 9x + 7

Solution

Problem 4 :

y = -3x2 + 12x - 10

Solution

Problem 5 :

y = 3x2 + 10x

Solution

Problem 6 :

y = x2 - 12x + 36

Solution

Problem 7 :

y = -4x2 - 24x - 15

Solution

Problem 8 :

y = -x2 - 4x - 1

Solution

1)

y = (x - 3)2 - 6

Vertex of the parabola is (3, -6).

2)

y = (x + 1)2 + 6

Vertex of the parabola is (-1, 6).

3)

y = (x + 9/2)2 - 49/4

vertex of the parabola is (-9/2, -49/4).

4)

y = -3(x - 2)2 + 2

The vertex of the parabola is (2, 2).

5)

y = 3(x + (5/6))2 - (25/12)

The vertex of the parabola is (-5/6, -25/12).

6)

y = (x - 6)2

the vertex of the parabola is (6, 0).

7)

y = -4(x + 3)2 + 21

So, the vertex of the parabola is (-3, 21).

8)

y = -(x + 2)2 + 3

So, the vertex of the parabola is (-2, 3).

## Recent Articles

1. ### Finding Range of Values Inequality Problems

May 21, 24 08:51 PM

Finding Range of Values Inequality Problems

2. ### Solving Two Step Inequality Word Problems

May 21, 24 08:51 AM

Solving Two Step Inequality Word Problems